2004
DOI: 10.4049/jimmunol.173.1.673
|View full text |Cite
|
Sign up to set email alerts
|

Age-Associated Change in the Frequency of Memory CD4+ T Cells Impairs Long Term CD4+ T Cell Responses to Influenza Vaccine

Abstract: We investigated the relationship of memory CD4+ T cells with the evolution of influenza virus-specific CD4+ T cell responses in healthy young and elderly people. Elderly individuals had a similar frequency of CD69+CD4+ T cells producing IFN-γ and TNF-α at 1 wk, but a lower frequency of these CD4+ T cells at 3 mo after influenza vaccination. Although the elderly had a higher frequency of central memory (CM; CCR7+CD45RA−) CD4+ T cells, they had a significantly lower frequency of effector memory (EM; CCR7−CD45RA−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
115
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(126 citation statements)
references
References 40 publications
8
115
2
1
Order By: Relevance
“…These results are in agreement with those of Aggarwal and Gupta, who showed that increased caspase-3 expression and decreased Bcl-2 expression in CD45RA + and CD45RO + T cells of aging humans mediated an increased susceptibility to apoptosis Gupta 1998, 1999). A possible explanation for the age-associated proneness to spontaneous apoptosis is the decreases in both IL-7 levels and IL-7 receptor with aging (Kim et al 2006;Kang et al 2004). The IL-7 pathway is necessary for the development and survival of memory T cells by upregulating Bcl-2 pro-survival proteins (Chetoui et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with those of Aggarwal and Gupta, who showed that increased caspase-3 expression and decreased Bcl-2 expression in CD45RA + and CD45RO + T cells of aging humans mediated an increased susceptibility to apoptosis Gupta 1998, 1999). A possible explanation for the age-associated proneness to spontaneous apoptosis is the decreases in both IL-7 levels and IL-7 receptor with aging (Kim et al 2006;Kang et al 2004). The IL-7 pathway is necessary for the development and survival of memory T cells by upregulating Bcl-2 pro-survival proteins (Chetoui et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study examined the generation of CD4 + memory T cells following influenza vaccination of young and aged adults [20]. This study found that the frequency of virusspecific CD4 + T cells from the peripheral blood that secreted IFN-γ or TNF-α upon ex vivo re-stimulation was significantly reduced in the elderly subjects three months postimmunization.…”
Section: Effect Of Age On Cd4 + T-cell-and Humoral-mediated Memorymentioning
confidence: 96%
“…We found that the following [10][11][12] and seasonal influenza vaccine. [13][14][15] Compromised nutritional status [16][17][18] and decreased T-cell activity [18][19][20] could be contributing factors for that finding. One study in patients with hepatitis C reported a decreasing effect of lower BMI on immune response to A(H1N1)pdm09 vaccine.…”
Section: Discussionmentioning
confidence: 99%